MICRO, SMALL AND MEDIUM ENTERPRISES (MSME) FINANCIAL MANAGEMENT IN INDONESIA AND MALAYSIA: A COMPARISON - Wardi, Jeni; N, Arizal; Siswati, Latifa; Yandra, Alexsander; Kadri, Halim Bin (Universitas Lancang Kuning, 2024)
This study examines the financial management of Micro Small and Medium Enterprises (MSMEs) in Indonesia and Malaysia which are the drivers of the economy in both countries, but this sector has not been able to become an independent sector and become the foundation of the national economy in both countries. The problem is that financial management in Micro Small and Medium Enterprises (MSMEs) ignores the importance of financial management standards, the problem is that poor financial management makes Micro Small and Medium Enterprises (MSMEs) insignificant in advancing the economy. The method used is descriptive qualitative with a case study approach. Data were obtained from MSME actors by distributing questionnaires and interviews. The results of this study indicate that MSME financial management in Indonesia is not as good as Micro Small and Medium Enterprises (MSMEs) in Malaysia, meaning that Malaysia has better MSME management, this can be seen from various research indicators, namely: planning indicators, budget use, recording, reporting and controlling. Micro Small and Medium Enterprises (MSMEs) in Indonesia and Malaysia when compared to Indonesian Micro Small and Medium Enterprises (MSMEs) do not have good planning, have not carried out standard records, standardized reporting, are not concerned with standard financial statements, balance sheets, profit and loss, cash flow, do not have or install systems in their business units, such as control of systems and procedures, billing records of sales notes, it is very clear that Micro Small and Medium Enterprises (MSMEs) in Indonesia have not done so. Meanwhile, from the other side, when compared to Indonesian MSME respondents, the level is very small, more so for micro cart businesses, small shops that are not in the form of their own buildings, the context is very small. In Malaysia, micro, small and medium enterprises are not comparable to the conditions in Indonesia, while in Malaysia, the Micro Small and Medium Enterprises (MSMEs) already have a more appropriate place. Thus, it is easier for Micro Small and Medium Enterprises (MSMEs) in Malaysia to get banking support, while Micro Small and Medium Enterprises (MSMEs) in Indonesia are still difficult to upgrade and are still difficult to enter the bank compared to Malaysia.